Implementasi Peerconnection Classifier Pada Jaringan dengan Menerapkan Load Balancing dan Failover - Nur, Rahmad; Suriati, Suriati; Syahputri, Nenna Irsa (Universitas Harapan Medan, 2025)
The internet has become a secondary necessity that supports daily activities such as working, studying, and exchanging information. High-traffic websites can overload servers, degrade performance, or cause system failures. One effective solution is to implement load balancing and failover methods. Load balancing divides the load across multiple servers to prevent overloading, while failover ensures the system stays functional by switching to backups in the event of a failure. This study aims to configure load balancing and failover on wireless networks using mikrotik devices and two internet modems. The test results showed that failover successfully maintained the connection when the main port was disabled, while load balancing increased internet speed by combining the main and backup networks.